Plant remains from an early Iron Age well at Hajndl, Slovenia - Šoštarić, Renata; Alegro, Antun, biolog; Hršak, Vladimir; Stančić, Zvjezdana; Kuester, Hansjoerg (2009)
Abstract: The archaeobotanical samples analysed derive from a well-preserved well dated to the Early Iron Age (Hallstatt) according to pottery found in the sampled layers and on a radiocarbon dating (720–520 cal B.C.) of the wooden construction of the well. Cultivated plants (Panicum miliaceum, Linum usitatissimum, Papaver somniferum and Camelina sativa) were recorded in relatively small numbers whereas primary cereals are lacking. Together with quite a large number of accompanied weeds they suggest agriculture activities, but a mixture of weeds and ruderal plants was probably also growing inside the relatively large settlement complex and could have been included in the assemblages just by chance. The plant species composition indicates local vegetation developed under strong anthropogenic influence and on mainly moist and nitrogen-rich soils. Grassland plants and an almost complete lacking of tree and shrub species characteristic for the climax vegetation (deciduous mesophilous mixed forests) of the region also indicate at least local human activity
Bibliografija: 37 jed
Sažetak
Keywords: Arheološko istraživanje -- Biljni ostaci; Rano željezno doba; Hajndl